2009
DOI: 10.1002/jhm.469
|View full text |Cite
|
Sign up to set email alerts
|

Patient readmissions, emergency visits, and adverse events after software‐assisted discharge from hospital: Cluster randomized trial

Abstract: Discharge software with CPOE did not affect readmissions, emergency department visits, or adverse events after discharge. Future studies should assess other endpoints such as patient perceptions or physician perceptions to see if discharge software has value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…A total of 12 studies published between 1992 and 2009 were considered unique and appropriate for final inclusion (figure 1). Study publications by Afilalo et al 6, Lang et al ,7 Callen et al 8 9 and Graumlich et al 10 11 reported data collected from common studies (and are therefore grouped in the tables below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 studies published between 1992 and 2009 were considered unique and appropriate for final inclusion (figure 1). Study publications by Afilalo et al 6, Lang et al ,7 Callen et al 8 9 and Graumlich et al 10 11 reported data collected from common studies (and are therefore grouped in the tables below).…”
Section: Resultsmentioning
confidence: 99%
“…Only four studies reported on primary outcomes: three reported on both readmission and mortality,10 13 16 one reported on readmission only,6 7 and two reported on actual or primary care physician (PCP) perceived reductions in adverse events/near misses 13 14. No significant differences in mortality were reported between groups at 30 days, 6 months or 12 months 10 13 16. Readmission/emergency department visits were similar between groups at 14 days, 28 days and 6 months,6 7 and were significantly lower in the intervention group at 12 months 16.…”
Section: Resultsmentioning
confidence: 99%
“…Graumlich and colleagues found no difference in readmission rates in a small randomized trial comparing a handwritten discharge document to an electronic discharge instruction form with medication reconciliation and automated communication to outpatient providers. 17 More recently, Jha et al reported no differences in 30-day readmission rates in CHF patients with and without disease-specific discharge instructions. 8 Grafft and colleagues showed no differences in readmission rates in general medicine patients with and without follow-up appointments documented on discharge instructions.…”
Section: Discussionmentioning
confidence: 98%
“…18 Initial attempts to improve inpatient test result management have not shown significant impact. 12,19 These results have illustrated that the workflow of hospital-based clinicians and the requirement to ensure follow-up of results after discharge from the hospital may necessitate different result management solutions for inpatient providers than those implemented in the ambulatory setting.…”
Section: Introductionmentioning
confidence: 99%